(untitled) (Global Journal of Medical Research, 2016)
Objective: To investigate the interaction between immune inflammatory response and sympathetic nervous system in the central regulation of chronic heart failure in rats. Methods: Branch ligation of the left anterior descending the making rat model of chronic heart failure, by AT1 receptor blockade losartan central intervention, intravenous injection of six Ting quaternary amines detected in rat basal sympathetic activity level, supersonic and enchanted figure for the detection of cardiac function, ELISA method for detection of plasma catecholamine and inflammatory factor levels. Results: Compared with the sham operation group, markedly enhanced the heart failure rat sympathetic nerve activity level, peripheral plasma TNF alpha, IL-1 beta and NE levels were significantly increased (P lt; 0.05) and cardiac dysfunction (P lt; 0.05); give AT1 receptor blocker losartan intervention RAS in central nervous system after the excessive enhancement of sympathetic nerve activity levels have decreased significantly, peripheral TNF alpha, IL-1 beta and NE levels were decreased (P lt; 0.05), cardiac function increased significantly (P lt; 0.05). Conclusion: Inhibition of RAS levels in the central nervous system in rats with chronic heart failure can reduce the CHF of the sympathetic system and peripheral immune response to inflammation, improve heart function.